2021
DOI: 10.3390/jimaging7070105
|View full text |Cite
|
Sign up to set email alerts
|

How Can a Deep Learning Algorithm Improve Fracture Detection on X-rays in the Emergency Room?

Abstract: The growing need for emergency imaging has greatly increased the number of conventional X-rays, particularly for traumatic injury. Deep learning (DL) algorithms could improve fracture screening by radiologists and emergency room (ER) physicians. We used an algorithm developed for the detection of appendicular skeleton fractures and evaluated its performance for detecting traumatic fractures on conventional X-rays in the ER, without the need for training on local data. This algorithm was tested on all patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The performance of the clavicle fracture classification model trained with our system is similar or better than models reported in the literature (see table 1. [33, 34] For example, Guermazi et al reported their AI model for identifying shoulder and clavicle fractures had a performance of 84% sensitivity, 83% specificity, and 0.90 AUC (95% CI 0.79-0.96). [14] Jones et al reported on a deep learning system for identifying clavicle fractures, using an ensemble of 10 convolutional networks, which obtained 90% sensitivity, 91% specificity, and an AUC of 0.96.…”
Section: Discussionmentioning
confidence: 99%
“…The performance of the clavicle fracture classification model trained with our system is similar or better than models reported in the literature (see table 1. [33, 34] For example, Guermazi et al reported their AI model for identifying shoulder and clavicle fractures had a performance of 84% sensitivity, 83% specificity, and 0.90 AUC (95% CI 0.79-0.96). [14] Jones et al reported on a deep learning system for identifying clavicle fractures, using an ensemble of 10 convolutional networks, which obtained 90% sensitivity, 91% specificity, and an AUC of 0.96.…”
Section: Discussionmentioning
confidence: 99%
“…Radiology has received much attention within clinical AI (Topol, 2019) and is the most advanced area of AI within orthopaedics (Langerhuizen et al., 2019). There is obvious appeal for the use of AI within hand and wrist surgery; for example, improving detection of scaphoid fractures (Yoon and Chung, 2021), which continue to elude clinicians, or for flagging hand and wrist fractures in general within emergency departments (Reichert et al., 2021). Such interventions could reduce the burden of emergency reporting in cases of binary decisions (fracture present or not present), reducing missed fractures and streamlining referral to orthopaedic clinics or automating further radiological investigations.…”
Section: Clinical Implementation Within Hand and Wrist Surgerymentioning
confidence: 99%
“…The radiologists’ performance was better than the AI’s for more severe diseases such as complete dislocations and aggressive FBL, whereas benign FBL and diastasis were rarely reported by them, likely because of their low clinical relevance. 46 In a separate study that examined whether deep learning can be used to improve fracture detection on X-rays in the Emergency Room, Reichert et al 47 used Azmed’s Rayvolve to detect traumatic fractures on the X-ray images of 125 patients. These patients were selected by two emergency physicians and the X-rays were also analyzed by a radiologist.…”
Section: Interpretative Uses Of Aimentioning
confidence: 99%